THE CORRELATION OF ENGLISH PROFICIENCY LEVEL AND TRANSLATION STRATEGIES USED BY INDONESIAN EFL LEARNERS - Delti Yulita (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
The importance of using translation to improve English language proficiency has been a debatable topic, specifically the effect of learners’ proficiency level in which dictate how the learners use the translation as a learning strategy. Thus, this study was purposed to find out the relationship between English proficiency level and EFL learners’ use of translation strategies. The Inventory for Translation as a Learning Strategy (ITLS) questionnaire was administered to 40 University students that divided into B2 and B1 based on CEFR level. One-way ANOVA results show that both learners are highly using translation as a learning strategy with mean score 3. Nonetheless, the significance difference was found in using translation to improve English skills such as reading, writing, speaking, and listening in which high proficient learners were less likely using translation strategies than low proficient. Furthermore, the correlation analysis shows the negative correlation between English proficiency and translation strategies and a positive correlation in using translation to find differences and similarities between L1 and L2. The pedagogical implications present that high and low proficient learners were benefited using translation strategies to enhance their English skills.